Nationalism Portrayed In Nagabonar Jadi 2 Movie: A Semiotic Analysis - Wahyu Unggul Widodo (Journalistics: Journal of English Teaching and Applied Linguistics, 2023)
Movie is one of the mass media in the form of audiovisual and its nature is very complex. The film became a social discourse with its characteristics spreading to many places. A movie may deliver certain messages to its audience. Movies in general also raise a topic or phenomenon occurring in society. “Nagabonar Jadi 2” is a comedy movie that portrays nationalism values in its scenes. This study used qualitative research methods using the method of content analysis. The main instrument of this study is the researcher himself, who conducts direct research such as watching, listening and understanding the movie, using Roland Barthes' semiotic theory, which focuses on the idea of two orders of signification. Besides having a general meaning, the movie also has a denotative meaning, connotative meaning and myth.